Structural model of in-group dynamic of 6-10 years old boys' motor fitness - O.V. Ivashchenko; T.S. Yermakova (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to determine structural model of in-group dynamic of 6-10 years old boys' motor fitness. Material: in the research 6 years old boys (n=48), 7 years old (n=45), 8 years old (n=60), 9 years' age (n=47) and10 years' age (n=40) participated. We carried out analysis of factorial model of schoolchildren's motor fitness. Results: we received information for taking decisions in monitoring of physical education. This information is also necessary for working out of effective programs of children's and adolescents' physical training. We determined model of motor fitness and specified informative tests for pedagogic control in every age group. In factorial model of boys' motor fitness the following factor is the most significant: for 6 years - complex development of motor skills; for 7 years - also complex development of motor skills; for 8 years - strength and coordination; for 9 years - complex development of motor skills; for 10 years - complex development of motor skills. Conclusions: In factorial model of 6-10 years old boys' motor fitness the most significant are backbone and shoulder joints' mobility, complex manifestation of motor skills, motor coordination. The most informative tests for assessment of different age boys' motor fitness have been determined.